In the Self's Place : the Approach of Saint Augustine. - Marion, Jean-Luc, 1946-; Kosky, Jeffrey (Palo Alto : Stanford University Press, 2012)
In the Self's Place is an original phenomenological reading of Augustine that considers his engagement with notions of identity in Confessions. Using the Augustinian experience of confessio, Jean-Luc Marion develops a model of selfhood that examines this experience in light of the whole of the Augustinian corpus. Towards this end, Marion engages with noteworthy modern and postmodern analyses of Augustine's most "experiential" work, including the critical commentaries of Jacques Derrida, Martin Heidegger, and Ludwig Wittgenstein. Marion ultimately concludes that Augustine has preceded postmoder.
Foreword; Bibliographic Note; Translator's Note; 1. Confessio or Reduction; 2. The Ego or the Gifted; 3. Truth, or the Saturated Phenomenon; 4. Weakness of Will, or Power of Love; 5. Time, or the Advent; 6. The Creation of the Self; 7. Addition: Idipsum, or the Name of God; Conclusion; Notes; English Translations Cited; Index locorum; Index nominum.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- Saint, Bishop of Hippo; Self (Philosophy); Augustine, Saint, Bishop of Hippo; Self (Philosophy); RELIGION -- Christian Theology -- Anthropology; Self (Philosophy); Electronic books